2017
DOI: 10.12659/msm.899804
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Restricts Coxsackievirus B Type 3 Replication via Inhibition of c-Jun N-Terminal Kinase (JNK) and p38 MAPK Activation In Vitro

Abstract: BackgroundAt present, the treatment of coxsackievirus-induced myocarditis remains difficult. Berberine (BBR), an isoquinoline alkaloid isolated from traditional medicine herbs, exhibits significant anti-viral efficacy against various viruses. However, the underlying mechanism by which BBR controls CVB3 infection has not yet been reported. The purpose of this study was to investigate the anti-viral efficacy of BBR against CVB3 infection and its mechanism.Material/MethodsIn our experiments, the protein levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, www.nature.com/scientificreports/ the atrial myocardial-endocardial separation observed at later stages in developing zebrafish embryos appears to coherently correlate with the reduced atrial contractility we reported during the earlier stages of development. As BRB was shown to influence myocardial cells, acting through the regulation of several molecular pathways 10,11 , it is possible to speculate that effects on this cell type may result, in turn, in the myocardial-endocardial detachment we observed. Finally, since the separation between these tissues may play an important role in various cardiac alterations in vertebrates, including the formation of pericardial edema 32,49 , it is possible to hypothesize that myocardial-endocardial detachment may play a role in pericardial edema development that we observed in BRB-treated embryos.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, www.nature.com/scientificreports/ the atrial myocardial-endocardial separation observed at later stages in developing zebrafish embryos appears to coherently correlate with the reduced atrial contractility we reported during the earlier stages of development. As BRB was shown to influence myocardial cells, acting through the regulation of several molecular pathways 10,11 , it is possible to speculate that effects on this cell type may result, in turn, in the myocardial-endocardial detachment we observed. Finally, since the separation between these tissues may play an important role in various cardiac alterations in vertebrates, including the formation of pericardial edema 32,49 , it is possible to hypothesize that myocardial-endocardial detachment may play a role in pericardial edema development that we observed in BRB-treated embryos.…”
Section: Discussionmentioning
confidence: 83%
“…BRB regulates multiple signaling pathways, and influences several cellular processes, including migration, proliferation, apoptosis and gene expression 4,6,[10][11][12][13][14] . Studies in rats and humans showed that BRB can be absorbed from the gastrointestinal tract after oral administration, although its bioavailability and plasma levels are very low.…”
mentioning
confidence: 99%
“…Activation of the MAP2K3/P38 MAPK signaling pathway is essential for CVB3 infection [5, 12, 13]. Our previous study showed that miRNA-21 that potentially targets MAP2K3 is upregulated in the heart of mice with CVB3-induced myocarditis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Virus elimination from vital organs is considered as a key therapeutic strategy to treat CVB3-associated diseases. However, currently available drugs for the treatment of CVB3 infection are broad-spectrum antiviral drugs with limited efficacy [3–5]. Therefore, understanding of the mechanisms involved in CVB3 infection may provide new clues for developing novel therapeutic strategies against CVB3-induced diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation